Analisis Pengaruh Visibility, Credibility, Attractiveness dan Power terhadap Keputusan Pembelian Produk MS Glow Skincare - Usi Apriliani; Budi Wahono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study was made to determine the effect of Visibility, Credibility, Attractiveness, Power on Purchase Decisions for MS Glow Skincare Products, the method used in this study is a quantitative method. Sampling in this study using the malhotra formula with a sample of 85 partisipants. The data used is primary data through a questionnaire. This study used instrument tests including: validity and reliability tests, normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, simultaneous tests and partial tests.From the results of the research partially obtained results where Visibility has no significant effect on purchasing decisions, Credibility has no significant effect on purchasing decisions, Attractiveness has no significant effect on purchasing decisions, Power has a significant effect on purchasing decisions. Simultaneously Visibility, Credibility, Attractiveness and Power has a significant effect on purchasing decisions. Keywords: Visibility, Credibility, Attractiveness, Power and Purchase Decisio